(Invited) Ultralow-Voltage Design and Technology of Silicon-on Thin-Buried-Oxide (SOTB) CMOS for High Energy Efficient Electronics in IoT Era. (27th March 2015) - Yamamoto, Yoshiki; Makiyama, Hideki; Yamashita, Tomohiro; Oda, Hidekazu; Kamohara, Shiro; Sugii, Nobuyuki; Yamaguchi, Yasuo; Mizutani, Tomoko; Kobayashi, Masaharu; Hiramoto, Toshiro
Abstract : We demonstrated ultralow voltage (<0.4V) operation of Silicon-on-Thin-Buried-oxide (SOTB) CMOS. Thanks to the small variability of SOTB Vmin of SRAM was lowered down to <0.4 V. Both fast access time and small standby leakage were achieved by adaptive back biasing (ABB). 32-bit RISC CPU operated at ultralow energy consumption of 13.4 pJ.